Menimbang Skala Prioritas dalam Kaidah Fikih : Antara Darurat dan Kebutuhan - Lisnawati Lisnawati; Maulina Maulina; Indra Ezha Noor Rizhal; Herlina Herlina; Al Nafis (Hidayah : Cendekia Pendidikan Islam dan Hukum Syariah, 2025)
Determining the scale of priorities in Islamic jurisprudence is an important method in decision-making in accordance with the principles of Islamic law. This principle is based on the rules of Islamic jurisprudence such as prioritizing obligatory obligations, prioritizing public interest, and preventing damage (dar'u al-mafāsid), which serve to balance individual needs and community interests. In this context, Islamic jurisprudence facilitates a systematic and proportional approach to various life problems. These principles emphasize that in order to achieve maqashid al-shariah (the goals of Islamic law), priority must be given to matters that are urgent, primary, and have the greatest and most sustainable benefits. Thus, the scale of priorities becomes an important instrument in ensuring justice, interest, and continuity in policy-making and actions. Understanding and applying these rules of Islamic jurisprudence enable Muslims to make decisions that are appropriate, balanced, and contextual, according to the situations and conditions faced. This study emphasizes the importance of the concept of the scale of priorities as a normative basis in realizing decisions that are just and beneficial for all people.